Chronique, fiction, roman de non-fiction - Florence Olivier (Caravelle)
Next to mass-medias’ diffusion of drug trafficking culture, as well as published journalistic investigations about the cartels, some authors of chronicles, novelists and storytellers looked for – and found – literary expressions that go beyond fascination and horror denunciation. The non-fiction novel Campos de amapola. Antes de esto by Lolita Bosch takes a clear and firm position against violence. Los trabajos del reino by Yuri Herrera bets upon fable’s poetry; Señor de Señores by Miguel Tapia parodies the Leviticus to evoke chastisement discourse. This paper deals with esthetic effects and eventual ethic interrogation of these works.